APPLICATION OF NAHWU IN ARABIC LANGUAGE LEARNING: A CASE STUDY OF BEGINNER STUDENTS - Neng Suryanti, Neng Suryanti; Lutfiana Sefira; Nurul Faizah (Sindoro: Cendikia Pendidikan, 2025)
This research discusses how the science of Nahwu is very important for learning Arabic. The science of Nahwu helps us understand how the meaning and structure of sentences change; this is very important to correctly interpret the meaning of the Arabic text. Learning Arabic includes elements such as vocabulary, grammar, phonology, and cultural context. All of these elements contribute to the ability to communicate well. In addition, this study found problems faced by beginners when learning Arabic. They found that it is essential to create a supportive learning environment. To improve student interaction and understanding, qiyasi and istiqraiyah methods are used in Nahwu learning. Structured memorization, practical exercises, and periodic evaluations are methods to improve student understanding. The results show that students' understanding of Arabic sentence structure can be improved by applying the right approach. This study emphasizes the need for a pen.